ANALISA YURIDIS HAK MENJUAL PEMILIK TANAH YANG BERASAL DARI HARTA BERSAMA - ROHANI RUSPITA ERITE SIMARSOIT SIMARSOIT (PREMISE LAW JURNAL, 2017)
ABSTRACT One of the properties which is commonly bequeathed is land. The problem arises when an heir wants to sell an inherited land he has received from his late father. The land certificate has not been transferred yet; let alone if there is more than one heir. They feel that they have been cheated since it is sold without their knowledge; therefore, they can file a complaint in civil case as it is stipulated in Article 1365 of the Civil Code which states that a person who violates law and harms other people has to compensate the loss. Keywords: Joint Property Transfer, by Heirs